Solvatochromic parameters of deep eutectic solvents formed by ammonium-based salts and carboxylic acids - Teles, Ana Rita R. (Fluid Phase Equilib, 2017)
Deep eutectic solvents (DES) have been studied in a wide range of applications, and despite their potential as sustainable solvents, detailed knowledge on their solvatochromic parameters is still lacking. To overcome this problem, in this work, the Kamlet Taft (KT) solvatochromic parameters, namely the hydrogen-bond acidity, hydrogen-bond basicity and dipolarity/polarizability, of a wide range of DES composed of ammonium-based salts as hydrogen bond acceptors (HBAs), and carboxylic acids as hydrogen bond donors (HBDs), were determined aiming at better understanding the influence of the chemical structure of the DES components on their polarity. It is shown that the high acidity of the DES investigated is mainly provided by the organic acid present in the mixture, and that an increase of the alkyl side chain of both the HBA and the HBD species leads to a lower ability of the solvent to donate protons. On the other hand, the ammonium salt plays the major role on the hydrogen-bond basicity of DES. Contrarily to the hydrogen-bond acidity, an increase in the length of the aliphatic moieties of both the carboxylic acid and salt cation results in solvents with higher ability to accept protons. The dipolarity/polarizability of DES is mainly defined by the ionic species present, and tend to decrease with the increase of the aliphatic moiety of the organic acid. In general, DES composed of ammonium-based salts and carboxylic acids present a higher capacity to donate and accept protons when compared to most of the ionic liquids or organic molecular solvents.